Examınatıon of the Relatıonshıp between Alexıthymıa, Anger and Defense Mechanısm - Kahraman Güler, Haydeh Faraji̇ (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction and Aim: It is thought that immature and neurotic defense mechanisms, especially splitting and introjection, play an important role in alexithymia. The aim of this study is to examine the relationship between alexithymia, anger and defense mechanisms in a non-clinical sample Materials and Methods: This study was prepared in accordance with the correlational survey model. The sample selection of the study was made using simple random sampling.The sample group of the study consists of 430 (50.1%) women and 427 (49.9%) men living in Istanbul.The research data collection process took place between 2019-2020. Results: There is a weak positive relationship between Anger Symptoms and Immature Defenses, and a weak and negative relationship with Mature Defenses. There is a weak and positive relationship between Situations Leading to Anger and Immature Defenses. There is a weak, positive relationship between Anger-Related Thoughts and Immature Defenses, and a moderate and negative relationship between Anger-Related Thoughts and Mature Defenses. There is a weak positive relationship between Anger-Related Behaviors and Imature Defenses, and a weak and positive relationship between Anger-Related Behaviors and Neurotic Defenses. Conclusion: It was determined that there is a significant relationship between the the sub-dimensions of the multidimensional anger scale and the sub-dimensions of the defense mechanisms and between the sub-dimensions of the multidimensional anger scale and the sub-dimensions of the Toronto alexithymia scale.